The impact of non-pharmacological therapies on cardiovascular outcomes in patients with refractory angina: a systematic review and meta-analysis of randomized controlled trials. (14th October 2021) - Verhemel, S; Jones, D A; Weeraman, D; Veerapen, J; Baumbach, A; Mathur, A
Abstract: : Despite advances in revascularization techniques and optimal medical management, refractory angina (RFA) represents an essential group of patients where progress has stalled, and in which therapeutic approaches remain uncertain. Numerous randomized control trials have reported clinical outcomes on a variety of treatments but to date no direct outcome comparison has been made. Our aim is to investigate and compare the outcomes of these different non-pharmacological technologies in RFA, centring on major adverse cardiac events and all-cause mortality. We performed a systematic review and meta-analysis of randomized controlled trials using the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. A comprehensive search was performed of PubMed, EMBASE (Excerpta Medica database), Cochrane, ClinicalTrials.gov, Google Scholar databases of randomized controlled trials, and scientific session abstracts. Studies were deemed eligible if they met the following criteria: (1) full-length publications in peer-reviewed journals; (2) evaluated non-pharmacological therapies use in patients with no further revascularization options while on optimal medical treatment; (3) patients had ongoing angina, Canadian Cardiovascular Society class II–IV; and (4) included a placebo/control arm. We calculated risk ratios for all-cause mortality, combined MACE events. We assessed heterogeneity using χ 2 and I 2 tests. We analysed 3292 citations with 51 randomized control trials testing 9 therapies including angiogenic proteins, stem-cell therapy, lipoprotein apheresis, coronary sinus reducer, spinal cord stimulator, percutaneous laser revascularization, shock-wave therapy, transmyocardial laser revascularization and enhanced external counter pulsation all meeting the inclusion criteria (table 1). Our analysis identified stem cell therapy as the only therapy with a reduction in all-cause mortality (Odds ratio, 0.45; CI, 0.21–1.00) (figure 1). A corresponding reduction in major adverse cardiac events (MACE) was also seen with stem cell therapy (OR 0.48: CI 0.30–0.75) alongside patients who received angiogenic proteins (OR 0.72: CI 0.55–0.93) and cardiac shockwave therapy (OR, 0.21: CI 0.10–0.46) Improvements in secondary measures of angina symptoms or frequency were seen with stem cell therapy, angiogenic proteins, coronary sinus reducer, spinal cord stimulator, shock-wave therapy, transmyocardial laser revascularization and enhanced external counterpulsation. This is the largest meta-analysis comparing outcomes of novel technologies used in refractory angina. This suggests that stem cell therapy is the only non-pharmacological therapy for RFA associated with a reduction in mortality, MACE and anginal symptoms. We propose further larger randomized control trials, to support these findings. Funding Acknowledgement: Type of funding sources: None.